IMPLEMENTATION OF LEAN MANUFACTURING TO MINIMIZE WASTE IN THE PROCESS OF PLASTIC BOX 260 USING VSM AND AHP METHOD - Roberth Marshall Ratlalan; Ishardita Pambudi Tama; Sugiono Sugiono (Journal of Engineering and Management in Industrial System, 2017)
Abstract one of the national manufacturing industry company engaged in the manufacture of military products with the resulting product is plastic box 260. To minimize the waste that occurs lean manufacturing approach is assisted by one of the tools in the concept of lean value stream mapping (VSM) aims to describe the overall Information from the flow of raw materials to finished products. Waste identification begins with the waste relationship matrix (WRM) and waste assessment questionnaire (WAQ) to determine the percentage of waste with the 3rd largest rank. Further analysis is done by analytical hierarchy process (AHP) aims to know the criteria of weighting from waste that has the highest ranking. The recommendation of improvement based on the analysis of waste with the 3 largest (unccessary inventory, overproduction, motion) and takt time calculation is to apply 5S, to apply forecasting, to add a working facility in the form of cooling room, to do maintenance activities such as preventive maintenance, addition of tools and machine, Setting laser machine, and layout design of production floor layout.